The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/mcn.12573
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation improves delivery of a nutrition‐sensitive agriculture programme in Burkina Faso

Abstract: Evidence is emerging from rigorous evaluations about the effectiveness of nutrition-sensitive agriculture programmes in improving nutritional outcomes. Additional evidence can elucidate how different programme components and pathways contribute and can be optimized for impact. The International Food Policy Research Institute, with Helen Keller International, designed a comprehensive framework to evaluate the delivery, utilization, and impact of Helen Keller International's enhanced homestead food production pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…In addition to having improved program designs, the new studies have tended to pay more attention than before to implementation quality, and a few of them documented working with researchers to design a program impact pathway framework (Rawat et al, 2013) and to measure, through process evaluations, implementation fidelity, quality of service delivery, quality of supervision structures, use of the program by targeted beneficiaries and perceptions and appreciation of the program from implementers and users (Olney et al, 2015(Olney et al, , 2016aOsei et al, 2017;Nielsen et al, 2017). The International Food Policy Research Institute (IFPRI) evaluates nutrition-sensitive programs (including nutritionsensitive agricultural programs) using a rigorous impact evaluation design, in addition to process evaluations using mixed methods in order to produce evidence on whether or not the programs being evaluated achieve the expected impacts on targeted outcomes, and also to answer the questions of how and why impacts are achieved (for detailed descriptions of the approach, see Menon et al, 2013;Rawat et al, 2013;Olney et al, 2017;Leroy et al, 2016).…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to having improved program designs, the new studies have tended to pay more attention than before to implementation quality, and a few of them documented working with researchers to design a program impact pathway framework (Rawat et al, 2013) and to measure, through process evaluations, implementation fidelity, quality of service delivery, quality of supervision structures, use of the program by targeted beneficiaries and perceptions and appreciation of the program from implementers and users (Olney et al, 2015(Olney et al, , 2016aOsei et al, 2017;Nielsen et al, 2017). The International Food Policy Research Institute (IFPRI) evaluates nutrition-sensitive programs (including nutritionsensitive agricultural programs) using a rigorous impact evaluation design, in addition to process evaluations using mixed methods in order to produce evidence on whether or not the programs being evaluated achieve the expected impacts on targeted outcomes, and also to answer the questions of how and why impacts are achieved (for detailed descriptions of the approach, see Menon et al, 2013;Rawat et al, 2013;Olney et al, 2017;Leroy et al, 2016).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…The International Food Policy Research Institute (IFPRI) evaluates nutrition-sensitive programs (including nutritionsensitive agricultural programs) using a rigorous impact evaluation design, in addition to process evaluations using mixed methods in order to produce evidence on whether or not the programs being evaluated achieve the expected impacts on targeted outcomes, and also to answer the questions of how and why impacts are achieved (for detailed descriptions of the approach, see Menon et al, 2013;Rawat et al, 2013;Olney et al, 2017;Leroy et al, 2016). The experience of the partnership between Helen Keller International (HKI) and IFPRI in working together over several years on evaluation and learning around a homestead food production system program implemented in Burkina Faso is described in Nielsen et al (2017).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Reflecting and Evaluating (Process) Evaluation challenges were cited in six studies as an implementation barrier (Gillespie et al 2015;Nielsen et al 2018;Legesse et al 2014;Carroll et al 2019;Pomeroy-Stevens et al 2016;Hodge et al 2015). Specifically, the lack of established mon-itoring or evaluation systems and absence of accountability for program targets were often cited as key issues (Hodge et al 2015;Gillespie et al 2015).…”
Section: Executing (Process)mentioning
confidence: 99%
“…In recent years, the importance of implementation research has emerged, 30 and some efficacy and effectiveness evaluations are including this type of research in their evaluation portfolios. 9,31,32 WFP has also begun to use this approach and has an example from a recent pilot study in Ethiopia. 33 The evaluation of newly designed nutrition-sensitive WFP programs should include rigorous process evaluations to assess implementation, operational, or utilization challenges that could jeopardize their impact.…”
Section: Key Components Developed For Wfp's Nutrition-sensitive Guidancementioning
confidence: 99%
“…The authors describe how barriers to optimal program implementation and uptake were identified through the process evaluation, shared with program implementers, and used to improve ongoing program implementation. 32 These plans should include presentations and publications of key results in appropriate fora and journals as well as translation of the research into action programmatically and potentially at the policy level.…”
Section: Next Stepsmentioning
confidence: 99%